Early Serologic Diagnosis of Mycoplasma pneumoniae Pneumonia: An Observational Study on Changes in Titers of Specific-IgM Antibodies and Cold Agglutinins - Lee, Sung-Churl (Medicine (Baltimore), 2016)
There have been some limitations on early diagnosis of Mycoplasma pneumoniae (MP) infection because of no immunoglobulin M (IgM) responses and variable detection rates of polymerase chain reaction in the early stage of the disease. We wanted to discuss regarding early diagnostic method using short-term paired titration of MP-specific IgM and cold agglutinins (CAs) in the early stage of MP pneumonia. The participants of this study were 418 children with MP pneumonia during 2 recent epidemics (2006–2007 and 2011), and they were diagnosed by an anti-MP IgM antibody test (Serodia Myco II) examined twice during hospitalization at presentation and around discharge (mean of 3.4 ± 1.3 days apart). CA titers were simultaneously examined twice during study period. Anti-MP IgM antibody titer ≥1:40 and CA titer ≥1:4 were considered positive, respectively. The relationships between 2 IgM antibodies in the early stage were evaluated. Regarding MP-specific antibody titers, 148 patients showed a seroconversion, 245 patients exhibited increased titers, and 25 patients had unchanged higher titers (≥1:640) during hospitalization. The median MP-specific antibody titers at each examination time were 1:80 and 1:640, respectively; those of CAs were 1:8 and 1:32, respectively. Illness duration prior to admission showed a trend of association with both titers, and patients with shorter illness duration had a higher rate of negative titers or lower titers at each examination time. CAs and MP-specific antibody titers were correlated in the total patients at presentation and at 2nd examination (P < 0.001, respectively), and the diagnostic corresponding rates of CAs to IgM antibody test were 81% to 96% in patient subgroups. Short-term paired MP specific-IgM determinations in the acute stage may be used as a definitive diagnostic method for MP pneumonia. Paired CA titers showed a correlation with MP-specific antibody titers, suggesting they can be used as an adjuvant diagnostic method.